A retrospective analytical study of treatment outcomes among multi drug resistant tuberculosis patients - Fatima, Sayed Shakita; Kumar , S; Verma , Ajay Kumar; Suryakant; Sachan , Amod Kumar; Dixit , Rakesh Kumar (Indian Journal of Community Health, 2021)
Background: India is amongst one of the high multidrug resistant tuberculosis (MDR-TB) burden countries globally with a huge contribution given by the state of Uttar Pradesh. Programmatic Management of Drug Resistant Tuberculosis, initiated in 2007 has taken over the disorganized and unsupervised treatment practice in India. However, regular scrutiny is required which points out both its success and failure. Aim & Objective: This study was conducted to evaluate final treatment outcomes among MDR-TB patients on standard Category IV regimen Settings and Design: Retrospective analysis was done using secondary data from medical records of all patients. Methods and Material: Data of all MDR-TB patients registered under RNTCP at King George’s Medical University, Lucknow from 2013 to 2016 was collected. Demographic details along with pre-defined treatment outcomes were recorded (cured, treatment completed, death, treatment failure, treatment default and transfer to higher centre). Statistical analysis used: Descriptive statistics using numbers and percentage. Results: The records of 3580 MDR tuberculosis patients registered at drug resistant tuberculosis centre in King George’s Medical University from January 2013 to December 2016 were included which consisted of 67%males and 33%female. Mean age of presentation was 31.17 years (95% CI 30.75-31.59). Mean weight of patients was 40.16 kg (95% CI 39.89-40.43). Year wise distribution of registered cases from 2013 to 2016 was 611, 799, 984 and 1186 patients respectively. Amongst 3580 patients, 30.39% were declared cured, 25.50% completed treatment, 21.39% died, 0.84% showed treatment failure, 12.54% were defaulters, 2.35% were transferred out to higher centre, 6.5% were shifted to regimen for Extensive drug resistant (EDR) TB, 0.16% patients needed to stop treatment due to ADR and 0.33% patient were still on treatment. Conclusion: The treatment success rate of MDR?TB patients is still low. Measures to improve treatment adherence as in National tuberculosis elimination programme (NTEP) attempts to further improve the success rate.